Dynamics of South Korea’s Three No’s Policy: Terminal High Altitude Area Defense (THAAD) Deployment and China Relations Analysis - Liani, Jihan Nadra; Rezasyah, Teuku; Heryadi, R. Dudy (Ilomata International Journal of Social Science, 2025)
This research analyzes the deployment of Terminal High Altitude Area Defense (THAAD) in South Korea’s foreign policy and its impact on relations with China. The study examines why South Korea took a compromising approach through the Three No’s Policy despite implementing the THAAD system as a deterrence against North Korea. Through James Rosenau’s Foreign Policy Theory with five factors (systemic, societal, governmental, idiosyncratic, and role sources), this research fills a gap in literature on decision-making dynamics in East Asian security dilemmas. The study employs qualitative methods with case study analysis, relying on primary and secondary sources including policy documents, official government statements, and bilateral economic data. Results indicate that economic dependence on China and domestic pressure became dominant factors in South Korea’s compromising decision, outweighing considerations of alliance with the United States. These findings imply that in an era of economic interdependence, even countries facing direct security threats may be forced to balance security interests with economic concerns.